Supply Chains Management Batu Mulia Khas Nusantara di Kotamadya Salatiga - Ricky Arnold Nggili; Rudolv Ronald Katayane (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2017)
Gemstones typical of the Nusantara in the Salatiga get a very large market and has many consumers militants. Though there is no production of gemstones typical of the Nusantara conducted in Salatiga. It is interesting to see the process of Supply Chain Management products are in the market in Salatiga. This study used qualitative methods to triangulate the analysis on data collected from dept interview, observation and documentation of data owned by the respondent. From the research and analysis of the data showed that the current SCM gemstones typical of the Nusantara in Salatiga includes two current SCM, ie from suppliers to resellers and end up in consumers. And current SCM to two, from the supplier to the consumer, and returned to the reseller as an expert in increasing the quality of the product value. From both the current approach, it appears that there is unity of the SCM process is realized by every chain SCM, as part of maintaining the continuity of the precious stone market in Salatiga. SCM flow is also supported by other supporting factors as an integral part, yet integrated with the SCM process. Supporting factors such as, integration, openness and sharing of information, a major supporter of specialty goods in the SCM process gemstones typical of the Nusantara in Salatiga.